Adjusting to chronic health conditions. [article]. - Helgeson, Vicki S.
Research on adjustment to chronic disease is critical in today's world, in which people are living longer lives, but lives are increasingly likely to be characterized by one or more chronic illnesses. Chronic illnesses may deteriorate, enter remission, or fluctuate, but their defining characteristic is that they persist. In this review, we first examine the effects of chronic disease on one's sense of self. Then we review categories of factors that influence how one adjusts to chronic illness, with particular emphasis on the impact of these factors on functional status and psychosocial adjustment. We begin with contextual factors, including demographic variables such as sex and race, as well as illness dimensions such as stigma and illness identity. We then examine a set of dispositional factors that influence chronic illness adjustment, organizing these into resilience and vulnerability factors. Resilience factors include cognitive adaptation indicators, personality variables, and benefit-finding. Vulnerability factors include a pessimistic attributional style, negative gender-related traits, and rumination. We then turn to social environmental variables, including both supportive and unsupportive interactions. Finally, we review chronic illness adjustment within the context of dyadic coping. We conclude by examining potential interactions among these classes of variables and outlining a set of directions for future research.- (from the author)